(untitled) (Research, Society and Development, 2020)
“Queijo de Manteiga” is a product of great consumption and socioeconomic value for the Brazilian Northeast. For its elaboration, the Legislation demands that the milk coagulation be done with organic acids; however, small producers perform the acidification with the natural milk microbiota. The objective of this work was to evaluate the use of microbial acidification with "LD" type starter culture, compared to direct acidification with the use of emulsifiers, on the chemical, physical and microbiological characteristics of the final product. The experiment was carried out in triplicate, representing independent processing. The treatments had no impact on the fat content of the cheeses, but the pH, moisture and ash content of the cheese made by direct acidification were higher (p≤0.05) than the cheese made by microbial acidification. The cheese made by direct acidification was less firm and less chewiness (p≤ 0.05). All cheeses complied with the established by IN number 60/2019, with fecal coliform count <3.0 MPN/g, absence of Salmonella sp and Staphylococcus spp <10.0 CFU/g. However, the lactic bacteria count was higher in the cheese made by microbial acidification. As it has a lower pH and a higher lactic acid bacteria count, it is possible that the “queijo de manteiga” obtained by microbial acidification has greater food security than the cheese made by direct acidification, since due to the milk bacteria, association with the production of bacteriocins, they have an inhibitory effect on the growth of pathogenic bacteria. Future studies should explore this hypothesis.